Incidence of healthcare-associated infections in intensive care of the emergency department of Oran in Algeria - Benbernou, Soumia; Ghoumari, Nabil; Kambouche, Fouzia; Kouadria, Rabah (International Journal of Medicine, 2024)
Introduction. Healthcare-associated infections (HAIs) are a serious problem of modern medicine. Patients hospitalized in intensive care units (ICUs) develop HAI significantly more often than patients in other hospital units.Materials and Methods.We carried out a retrospective study spread over 2 years from January 2019 to December 2021. Data were collected on a form established with the microbiology department of the the University Hospital center of Oran, sites of nosocomial infection, germs involved, antibiotic resistance.Results: 886 samples were collected during the study period, of which 660 were positive. 270 patients were admitted to hospital during this period. The average age of our patients was 39.4 years. The most frequently isolated bacteria were Klebsiella pneumoniae ,Acinetobacter baumannii ,Staphylococcus aureus ,and Escherichia coli .Conclusion Infection control based on incidence rate for each type of infection is necessary in ICU to assess the epidemiological situation.